2013
DOI: 10.7860/jcdr/2013/7720.3882
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Detection of p16 INK4a in Leukoplakia and Oral Squamous Cell Carcinoma

Abstract: Introduction: Over-expression of p16 INK4a has been reported in tissues of oral squamous cell carcinoma (SCC) associated with Human Papillomaviruses (HPVs). Immunohistochemical (IHC) detection of p16 INK4a is an easy technique than molecular detection of HPVs, hence we investigated the presence of this protein in the most common pre-malignant and malignant oral lesions i.e. leukoplakia and SCC respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…Agrawal et al detected p16 in 85.71% cases of OSCC and suggested p16 as a surrogate marker for HPV presence in OSCC and OED; however, the sample size was much less ( n = 20) for establishment of p16 as surrogate marker. The other study by Prakash et al also identified a high positivity of p16 in OSCC (71%), but they did not detect HPV in these cases. So overexpression of p16 cannot be suggested due to HPV infection.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Agrawal et al detected p16 in 85.71% cases of OSCC and suggested p16 as a surrogate marker for HPV presence in OSCC and OED; however, the sample size was much less ( n = 20) for establishment of p16 as surrogate marker. The other study by Prakash et al also identified a high positivity of p16 in OSCC (71%), but they did not detect HPV in these cases. So overexpression of p16 cannot be suggested due to HPV infection.…”
Section: Discussionmentioning
confidence: 71%
“…Only two studies conducted in India exhibited correlation between HPV and p16 status in oral cancer . Agrawal et al detected p16 in 85.71% cases of OSCC and suggested p16 as a surrogate marker for HPV presence in OSCC and OED; however, the sample size was much less ( n = 20) for establishment of p16 as surrogate marker.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies analysed the impact of HPV infection on head and neck cancer with HPV positivity in 24%–73% of the investigated tumours (Jalouli et al., ; Mathew et al., ; Ostwald et al., ; Prakash et al., ). Although the role of HPV infections in the pathogenesis of oropharyngeal cancers is proven, the impact of oral HPV infection on development of OSCC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies analysed the impact of HPV infection on head and neck cancer with HPV positivity in 24%-73% of the investigated tumours (Jalouli et al, 2010;Mathew et al, 2011;Ostwald et al, 2003;Prakash et al, 2013). Although the role of HPV infections in could be shown, which was previously described mainly for OPSCC (Fakhry et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…p16 immunoexpression has similarly yielded variations in HPV presence in PPOELs. 61 It might have been expected that a strong link between HPV and PPEOLs would be reflected in a higher rate of HPV (particularly oncogenic types) in erythroplakia than in leukoplakia, but HPV infection rates in the former (although not evaluated to any notable extent) seem to be of similar rates as those of the latter. 62 An early meta-analysis of case reports and case series showed that HPV is 3 times more likely to be detected in PPOELs and 4.7 times more likely to be identified in OSCC than in the normal mucosa.…”
Section: Oral Submucous Fibrosismentioning
confidence: 99%